Implementation of Sekolah Penggerak Programs as Strengthening Profile Pancasila Students Through Digital Literacy at SMP Negeri 48 Samarinda - Almasari Aksenta; Tandi Kadang (Puslitbang Akademi Relawan TIK Indonesia (ARTIKA), 2024)
SMP Negeri 48 Samarinda is one of the model schools of the Sekolah Penggerak in Samarinda . The school has a routine program which must support the vision and mission of the Ministry of Education and Culture, namely strengthening the Pancasila Student Profile. Based on these values, the school holds activities related to strengthening the field of technology. The school collaborates with the East Kalimantan ICT Volunteer Academy (Artika) to carry out the activities of this program. The activity was carried out with lectures and resource persons from Artika, East Kalimantan. Participants in this activity were students from SMP Negeri 48 Samarinda . This activity aims to provide an understanding of current technological literacy, namely digital technology. This activity, which runs for only one day, is expected to provide additional knowledge to students and is in accordance with the values running in the school program.